PENAMPILAN FENOTIP DAN BEBERAPA PARAMETER GENETIKA GENOTIP JAGUNG KOMPOSIT DI GORONTALO PERFORMANCE OF PHENOTYPE AND SOME GENETIC PARAMETERS OF COMPOSITE MAIZE GENOTYPE IN GORONTALO - Rusliyadi, M. ; Azra, M. (Pembangunan Pedesaan, 2009)
The objective of this research was to evaluate phenotypic performance and genetic parameter of yield character, yield components, and growth of composite maize in Gorontalo. Fourteen maize genotypes from Balitser and two comparer varieties were sown for evaluation from August 2007 up to November 2007 using a randomized block design with three replication. Result of the research indicated that seven genotypes gave higher yield than Sukmaragaocal (comparer-2), namely, MSK 2 (RSS) C5, MS - 1, MS 3, BK (HS) C2, MSJ 2 (RRS) C5, MSJ 1 (RRS) C6, and SATP - 1 (S2) C7. No genotypes produced lower yield than Lamuru (comparer-1). Two genotypes showed higher yield of 7 t ha , namely, MS - 1 (7.01 t ha) and MSJ 1 (RRS) C6 (7.33 t ha ). Values of coefficient of variance from all characters were lower except for downy mildew percentage. High heritability estimate was observed for 50% male and female flowering and downy mildew percentage while for other characters were medium category, except for ASI (Anthesis-silking interval). Ear placement and weight of 1,000 grain had significant and positive correlation with yield, while downy mildew percentages had negative correlation with yield.